Serine 298 Phosphorylation in Linker 2 of UHRF1 Regulates Ligand-Binding Property of Its Tandem Tudor Domain. Issue 14 (26th June 2020) - Kori, Satomi; Jimenji, Tomohiro; Ekimoto, Toru; Sato, Miwa; Kusano, Fumie; Oda, Takashi; Unoki, Motoko; Ikeguchi, Mitsunori; Arita, Kyohei
Abstract: Ubiquitin-like with PHD and RING finger domains 1 (UHRF1) is an essential factor for the maintenance of mammalian DNA methylation and harbors several reader modules for recognizing epigenetic marks. The tandem Tudor domain (TTD) of UHRF1 has a peptide-binding groove that functions as a binding platform for intra- or intermolecular interactions. Besides the groove interacting with unphosphorylated linker 2 and spacer of UHRF1, it also interacts with di/tri-methylated histone H3 at Lys9 and DNA ligase 1 (LIG1) at Lys126. Here we focus on the phosphorylation of Ser298 in linker 2, which was implied to regulate the ligand-binding property of the TTD. Although the protein expression level of UHRF1 is unchanged throughout the cell cycle, Ser298 phosphorylated form of UHRF1 is notably increased in the G2/M phase, which is revealed by immunoprecipitation followed by Western blotting. Molecularly, while unphosphorylated linker 2 covers the peptide-binding groove to prevent access of other interactors, small-angle X-ray scattering, thermal stability assay and molecular dynamics simulation revealed that the phosphate group of Ser298 dissociates linker 2 from the peptide-binding groove of the TTD to permit the other interactors to access to the groove. Our data reveal a mechanism in which Ser298 phosphorylation in linker 2 triggers a change of the TTD's structure and may affect multiple functions of UHRF1 by facilitating associations with LIG1 at DNA replication sites and histone H3K9me2/me3 at heterochromatic regions. Graphical abstract: Unlabelled Image Highlights: Ser298 in linker 2 of UHRF1 TTD underwent phosphorylation in G2/M phase. Dominant binding of linker 2 to the TTD was released by Ser298 phosphorylation. Other interacting proteins could bind to the phosphorylated TTD. Ser298 phosphorylation enhanced structural heterogeneity of linker 2.